109 Marked Differences in the Pharmacodynamics of Modern P2Y12 Inhibitors in Patients Undergoing Treatment for ST Segment Elevation MI (STEMI) and Non ST Segment Elevation MI (NSTEMI). (3rd June 2016) - Amoah, Vincent; Khan, Nazish; Smallwood, Andrew; Wrigley, Ben; Martins, Joe; Khogali, Saib; Munir, Shahzad; Alan, Nevill; Cotton, James
Abstract : Introduction: Current pharmacodynamic (PD) data suggest reduced antiplatelet effect in ST-Elevation myocardial infarction (STEMI) of prasugrel and ticagrelor. We sought to investigate the early PD effect of prasugrel and ticagrelor administered in two patient groups: those admitted with STEMI and a cohort admitted with NSTEMI/unstable angina (UA). Methods: P2Y12 inhibitor naïve patients presenting with STEMI or NSTEMI/UA were assessed for inclusion. All patients provided informed consent. All received aspirin (300mg) and loading dose of either prasugrel (60mg) or ticagrelor (180mg) in a non-randomised fashion. Platelet reactivity was measured using VerifyNow assay at 20 min, 1 and 4 h post loading. Results are expressed a P2Y12 reaction units (PRU). PRU≥208 indicates a sub optimal antiplatelet response. PRU over time was tested between groups using 2 way ANOVA, P < 0.05 was considered significant. Results: A total of 58 patients were enrolled (30 STEMI, and 28 NSTEMI/UA Table 1 ). Results are shown in Fig 1 . In the STEMI patients there was little effect of either agent at 20 min post loading (prasugrel PRU 247 + 48.8, ticagrelor PRU 256 + 50.8) with a limited effect at 1 h and persisting attenuated results at 4 h. In the NSTEMI group however there was a marked and rapid antiplatelet effect of both agents at all time points. Over time there was a significant difference between the effect of both prasugrel ( P < 0.001) and ticagrelor ( P < 0.001) in STEMI patients vs NSTEMI patients. There was no significant difference in the effect of ticagrelor vs prasugrel over time in either STEMI or NSTEMI/UA. Conclusion: Prasugrel and ticagrelor in the context of STEMI do not provide adequate P2Y12 inhibition at reperfusion and the first hour post loading when compared to patients with NSTEMI/UA.